METAL CORD WITH FULL PENETRATION OF RUBBER COMPOUND INTO STRUCTURE - A. V. Vedeneev (Литьë и металлургия)
It is shown, that perspective direction of further development of metal cord constructions for tires breakers is embedding of metal cord of type «Betru» or FRP.